Safety and efficacy of radiotherapy combined with lenvatinib plus PD-1 inhibitors as neo-adjuvant therapy in hepatocellular carcinoma with portal vein thrombus: protocol of an open-label, single-arm, prospective, multi-center phase I trial - Li, Guangxin; Shu, Bin; Zheng, Zhuozhao; Yin, Hongfang; Zhang, Chen; Xiao, Ying; Yang, Yanmei; Yan, Zhe; Zhang, Xiaofei; Yang, Shizhong; Li, Gong; Dong, Jiahong (Frontiers in Oncology, 2022)
Background Surgical resection is a mainstay to treat hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT) in east Asia. However, the postoperative recurrence rate is high. It is necessary to explore neo-adjuvant therapy to increase the surgical resection rate and improve overall survival. Evidence has shown that lenvatinib combined with PD-1 inhibitors is safe and effective in the treatment of advanced unresectable HCC. Radiotherapy is also an effective treatment method for PVTT and has a synergistic effect in combination with PD-1 inhibitors. Surgical resection after Lenvatinib and sintilimab combined with radiotherapy as a neoadjuvant treatment regimen may be a new exploration of HCC with PVTT, but there were not any reported. Methods This open-label, single-arm, prospective, multi-center Phase I trial will enroll 20 HCC patients with PVTT who have a resectable primary tumor and no extra-hepatic metastasis. Eligible patients will be given radiotherapy, 3Gy*10 fraction, and will receive lenvatinib 8-12mg once daily and sintilimab 200mg once every three weeks. Surgical resection will be performed 6-8 weeks after radiotherapy. The primary endpoint is safety (number of patients ≥3G TRAE) and the number of patients who complete pre-op treatment and proceed to surgery. The secondary study endpoints include Major Pathological Response (MPR), 1-year tumor recurrence-free rate, Objective Response Rate (ORR), Imaging-Pathology Concordance Rate (IPCR), PVTT regression rate, Median Overall Survival (OS) and Recurrence Free Survival (RFS). Discussion This trial may confirm that surgical resection following intensive neoadjuvant therapy can provide a safe and efficient regimen for BCLC stage C patients with PVTT. Clinical trial registration https://clinicaltrials.gov/, identifier (NCT05225116).